(untitled) (Research, Society and Development, 2020)
Objective: the general objective of addressing the difficulties experienced by man in the prevention of prostate cancer. Methods: This is a literature review that allows for an analysis of the knowledge already built in research, the healthy database, Nursing Database (BDENF), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Libracy Online (SCIELO). Results: The obstacles that men encounter in health services, being ashamed to expose themselves, being justified by male behavior in not adhering to preventive measures and health promotion. Conclusion: In view of this initiative, the spaces fostered for the promotion of men’s health should be expanded to include hospital-level care, which is pertinent as men, unlike women, search for health services in their the vast majority, for urgent / emergency care and not for scheduled and deliberate care for health maintenance.